Long-chain Omega-3 fatty acids supplementation and cognitive performance throughout adulthood: A 6-month randomized controlled trial. (March 2022) - Maltais, Mathieu; Lorrain, Dominique; Léveillé, Pauline; Viens, Isabelle; Vachon, Annick; Houeto, Anita; Presse, Nancy; Plourde, Mélanie
Highlights: A 6-month n-3 PUFA supplementation did not improve cognitive performance in cognitively healthy adults. APOE carriers and age were not effect modifiers for any outcomes. Those with low baseline memory scores might benefit more from the n-3 PUFA supplement. Abstract: Objective: To investigate whether omega-3 polyunsaturated fatty acids (n-3 PUFA) supplementation improve cognitive performance and if apolipoprotein E (APOE) genotype or age were effect modifiers. Methods: Healthy adults of 20 to 80 years old ( n = 193) were completed a 6-month double-blind randomized controlled trial with two groups: 2.5 g/day of n-3 PUFA or a placebo. Primary outcomes were visuospatial ability and working memory and secondary outcomes were episodic memory and executive function, measured at baseline and 6 months. Results: Cognitive performances did not significantly differ between groups on primary or secondary outcomes after 6 months of treatment. APOE carriers and age were not effect modifiers for any outcomes. Those with low episodic memory scores and taking the n-3 PUFA supplement, significantly improved their scores ( p = 0.043). Conclusions: A 6-month n-3 PUFA supplementation did not improve cognitive performance in cognitively healthy adults and APOE status or age were not effect modifiers.